Determining the Effect of Electromagnetic Field-assisted Freezing on Shelf-stability of Beef Striploins - Jordan T. Looper (Kansas Agricultural Experiment Station Research Reports, 2026)
Objective: The objective of this study was to determine the effect of electromagnetic (EM) field-assisted freezing on beef color stability during the retail display of previously frozen beef striploins. Study Description: Striploins were collected from both sides of 12 USDA Choice carcasses and halved. Each half was randomly assigned to 0 kV, 2 kV, 4 kV, or 8 kV and then frozen for 24 hours at -4°F under the designated continuous EM field treatment. Halves were thawed at 36°F for 72 hours and then cut into steaks. One 1-in. and four ½-in. steaks were overwrapped for a 10-day simulated retail display. Instrumental and descriptive color measurements were taken daily. Thiobarbituric acid reactive substances (TBARS) assay for lipid oxidation and oxygen radical absorbance capacity (ORAC) tests for antioxidant capacity were conducted. The Bottom Line: The 4 kV group showed better color stability objectively and subjectively throughout the display period and a higher hydrophilic antioxidant capacity, but the mechanisms behind this finding are unknown.
Keywords: electromagnetic field; freezing; color